The Val66Met variant of brain-derived neurotrophic factor is linked to reduced telomere length in a military population: a pilot study - Richard C. Allsopp; Lisa M. Hernández; Marcus K. Taylor (Scientific Reports)
Abstract In military populations, gene-environment interactions can influence performance and health outcomes. Brain-derived neurotrophic factor (BDNF) is a central nervous system protein that is important for neuronal function and synaptic plasticity. A BDNF single nucleotide polymorphism, rs6265, leads to an amino acid substitution of valine (Val) with methionine (Met) at codon 66 (Val66Met), which may influence an individual’s response to occupational stress, and predispose military members to psychological disorders. Telomere length (TL), a novel measure of biological aging, can be used as a biomarker of stress. Accordingly, telomere shortening may be a surrogate indicator of physiological weathering due to chronic disease and stressful life events. To increase our understanding about the potential effect of the Val66Met mutation on the human stress response, we evaluated the relationships between Val66Met, TL, and mental health symptoms in a military population. In this pilot study (N = 164), we observed an association between Val66Met and reduced TL (p = 0.048). There was no relationship between Val66Met and mental health symptoms. These results support the investigation of gene-environment interactions, and their potential influence on TL due to occupational stress such as military service.